Nutrient Management Strategies on Heterogeneously Fertile Granitic‐Derived Soils in Subhumid Zimbabwe. (1st May 2015) - Kurwakumire, Natasha; Chikowo, Regis; Zingore, Shamie; Mtambanengwe, Florence; Mapfumo, Paul; Snapp, Sieglinde; Johnston, Adrian
Abstract : Maize ( Zea mays L.) is the staple food in southern Africa, but low soil fertility and lack of effective fertilization strategies for variable soil conditions hamper efficient use of nutrient resources. The objective of this study was to establish the influence of soil fertility heterogeneity on maize yield response to manure, liming, and inorganic fertilizers. Three sites, selected to represent three soil fertility domains based on soil organic carbon (SOC) between 3.5 to 8.9 g SOC kg −1 soil, were used during two cropping seasons. Nitrogen, P, K, and S were applied alone (NPKS) or in combinations involving lime, cattle manure, and micronutrients. Grain and stover were analyzed for nutrient uptake, and agronomic efficiencies were computed for N and P. Across sites, maize grain yields increased with increasing SOC. In Year 2, lime was the most important component for increasing maize yields in low SOC soil. For the medium and high SOC soils, treatments with NPKS + manure resulted in the best efficiencies. Although soil pH was low in these fields as well, lime which was applied only in Year 1, did not improve yields either year. Maize yields and nutrient uptake were strongly affected by SOC content, with yields for a site with 3.5 g SOC kg −1 soil significantly lower than the two sites that had >5.3 g SOC kg −1 soil. We conclude that farmers must strategically target their limited nutrients resources to fields that are not yet degraded and maintain soil fertility to guarantee returns to fertilizer investments.